Citronellol-functionalized natural silica: a biogenic approach for antifungal and antibacterial material applications - López, Guillermo Pablo (2025)
Introduction: New bioactive hybrid materials to prevent biofilm-induced biodeterioration are a significant challenge in indoor environments, where contaminants from microbial films compromise structural integrity and contribute to air pollution, posing health risks from prolonged exposure to biological agents. Methods: For the first time, diatomaceous earth or diatomite (Dt) was functionalized with quaternary ammonium salt (QAS) and a biogenic compound, citronellol, to develop a bioactive hybrid material (Dt*QC). The hybrids obtained were characterized by thermogravimetric analysis (TGA), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and Fourier-transform infrared spectroscopy (FTIR). The antifungal and antibacterial activity were assessed by agar diffusion assay, and micro/macrodilution tests. Results and Discussion: Characterization confirmed successful functionalization. TGA revealed organic contents of 50.9% with citronellol incorporation reaching 48.1%. SEM-EDS corroborated the incorporation of organic components. FTIR further verified the integration of functional groups while preserving the structural stability of the siliceous framework. Antimicrobial assays revealed a broader range of activity for Dt*QC. For bacterial strains, Dt*QC achieved a minimum inhibitory concentration (MIC) of 0.15 mg/mL against Staphylococcus aureus and demonstrated over 99.9% bacterial reduction, even at lower concentrations. This study highlights a novel approach to developing antimicrobial materials by functionalizing Dt with QAS and citronellol. Overall, these findings underscore the potential of Dt*QC as an advanced antimicrobial material for applications in coatings and preservation systems, offering a sustainable solution to prevent biodeterioration and microbial contamination.